2013
DOI: 10.1364/boe.4.002411
|View full text |Cite
|
Sign up to set email alerts
|

Extended hierarchical Bayesian diffuse optical tomography for removing scalp artifact

Abstract: Abstract:Functional near-infrared spectroscopy (fNIRS) can noninvasively measure hemodynamic responses in the cerebral cortex with a portable apparatus. However, the observation signal in fNIRS measurements is contaminated by the artifact signal from the hemodynamic response in the scalp. In this paper, we propose a method to separate the signals from the cortex and the scalp by estimating both hemodynamic changes by diffuse optical tomography (DOT). In the inverse problem of DOT, we introduce smooth regulariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The regularization effect becomes dominant as the absorption change is located in a deeper area, since the observed light-intensity change weakens with depth relative to the regularization effect. The same phenomenon was also observed in our previous study [20]. The above results of the simulation experiment showed that multi-directional DOT was accurate up to a 15-mm depth.…”
Section: Simulation Experimentssupporting
confidence: 89%
See 2 more Smart Citations
“…The regularization effect becomes dominant as the absorption change is located in a deeper area, since the observed light-intensity change weakens with depth relative to the regularization effect. The same phenomenon was also observed in our previous study [20]. The above results of the simulation experiment showed that multi-directional DOT was accurate up to a 15-mm depth.…”
Section: Simulation Experimentssupporting
confidence: 89%
“…Thus, visualization by multidirectional DOT is limited to areas around the cortical surface. By contrast, because many distinct optical paths exist in a shallow area enough to reconstruct a three-dimensional image, it would be possible to utilize such a method that reconstructs a scalp's hemodynamic change as well as a cortical hemodynamic change and remove the former [9,10,20]. The results also show that estimation was difficult in the distant area of the rectangular arrangement (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work is needed to quantify the impact of extracerebral hemodynamic changes on fNIRS signals as well as to develop appropriate methods to reduce this confounding factor. Useful approaches were already developed (e.g., [Berger et al, 2012;Gagnon et al, 2014;Haeussinger et al, 2014;Jelzow et al, 2014;Saager et al, 2011;Saager and Berger, 2008;Scarpa et al, 2013;Shimokawa et al, 2013;Tanaka et al, 2013;Yamada et al, 2012;Zucchelli et al, 2013]) that could be used for future fNIRS studies about similar aspects as analyzed in the present study.…”
Section: The Importance Of a Realistic Interpretation Of The Fnirs Simentioning
confidence: 99%
“…In recent years, functional near-infrared spectroscopy (fNIRS) has been used as an alternative non-invasive brain imaging technique to fMRI [10][11][12][13][14][15]. fNIRS determines the concentration changes of oxy-hemoglobin (HbO) and HbR in tissues by measuring lightabsorption variations at multi-wavelengths [16].…”
Section: Introductionmentioning
confidence: 99%